A lord lieutenant in wartime : the experiences of the fourth Earl Fortescue during the First World War - Batten, Richard, 1964- eeditor (Devon and Cornwall Record Society (Series), 2018)
This book is a study of the British Home Front of the First World War, on a local level, from the perspective of the Lord Lieutenant of Devonshire: the fourth Earl Fortescue. As a Lord Lieutenant during the Great War, Hugh Fortescue was a pre-eminent figure in Devon's local elite, to which his involvement with the war effort in the county was significant. This volume considers the wartime experiences of a county's Lord Lieutenant through a presentation of records from Fortescue's private papers. It contains the original typescript that Earl Fortescue wrote in 1924 as a retrospective account of his experiences during the conflict and the diaries that he kept from 1914 to 1918. In particular, the wartime diaries of the fourth Earl Fortescue are a rich, insightful and multifaceted account of Earl Fortescue and the Fortescue family during the war years. Alongside the original typescript and his wartime diaries, this book also presents a selection of documents related to the Great War from the Fortescue at Castle Hill archive. By presenting these documents from Lord Fortescue, this book raises awareness of his involvement with the war effort in the county and the momentous challenges that he faced as the Lord Lieutenant of Devon during the First World War.